The Influence of Game-Based Learning Method on the Positive Attitudes of Eleventh Grade Students in Islamic Religious Education at Senior High School Muhammadiyah 1 Pontianak for the 2025/2026 Academic Year - Dina Aprilia Wati; Wahdah Wahdah; Elin B. Somantri (Journal of Social Research, 2026)
This study aims to investigate and analyze the effect of the application of the Game-Based Learning (GBL) method on the positive attitudes of Grade XI students in the subject of Islamic Religious Education (Pendidikan Agama Islam/PAI) at SENIOR HIGH SCHOOL Muhammadiyah 1 Pontianak for the 2025/2026 Academic Year. The research method employed is quantitative with a quasi-experimental design. The research population comprised all Grade XI Social Studies (Ilmu Pengetahuan Sosial/IPS) students, with samples selected using a purposive sampling technique, namely Class XI IPS 1 as the experimental group and Class XI IPS 2 as the control group. Data were collected through a questionnaire measuring three indicators of positive attitudes: perceptions of teachers and instructional methods, responsibility toward academic tasks, and consistency of learning behavior. The data analysis technique applied was the Mann-Whitney U non-parametric statistical test, as the data did not satisfy the assumption of normal distribution. The results revealed that the positive attitude of students in the control class fell within the moderate category, with a mean score of 77.83, while the experimental class achieved the good-to-very-good category, with a mean score of 89.63. The hypothesis test yielded an asymptotic significance value of Asymp. Sig. (2-tailed) = 0.001 < 0.05; therefore, H0 is rejected and Ha is accepted. It can thus be concluded that the application of the Game-Based Learning method has a significant positive influence on the improvement of students' positive attitudes in PAI subjects at Senior High School Muhammadiyah 1 Pontianak.